The Pathobiome in Animal and Plant Diseases. (November 2019) - Bass, David; Stentiford, Grant D.; Wang, Han-Ching; Koskella, Britt; Tyler, Charles R.
Abstract : A growing awareness of the diversity and ubiquity of microbes (eukaryotes, prokaryotes, and viruses) associated with larger 'host' organisms has led to the realisation that many diseases thought to be caused by one primary agent are the result of interactions between multiple taxa and the host. Even where a primary agent can be identified, its effect is often moderated by other symbionts. Therefore, the one pathogen–one disease paradigm is shifting towards the pathobiome concept, integrating the interaction of multiple symbionts, host, and environment in a new understanding of disease aetiology. Taxonomically, pathobiomes are variable across host species, ecology, tissue type, and time. Therefore, a more functionally driven understanding of pathobiotic systems is necessary, based on gene expression, metabolic interactions, and ecological processes. Highlights: Animal and plant diseases are increasingly recognised to result from interactions between host-associated bacteria, eukaryotes, and viruses, their host, and the environment. The diversity and function of host-associated organisms are diverse and incompletely understood. Multidisciplinary studies, including high-throughput sequencing 'omics, can be used to reveal both the structure and function of pathobiomes, which may not be discernible from taxonomic analyses alone. Both 'normal' and 'disease' pathobiomes vary over time and between host tissues and organs. Understanding pathobiotic systems presents not only challenges to current disease diagnostic practices and legislation associated with this, but also diverse new opportunities for mitigating disease and optimising on-farm growing conditions.